Analisis Penerimaan Pajak Restoran dan Pajak Hotel Sebagai Sumber Pendapatan Asli Daerah (Studi Pada Dinas Pendapatan Pengelolaan Kekayaan Asli Daerah Kota Surakarta) - Budi, Destarika Isnaani Latifah Setyo, Drs. Agus Endro Suwarno , M.Si (2017)
The Local Genuine Income (PAD) is a source of local income which may consist of local tax, local retribution, separated local wealth management, and others. Restaurant Tax and Hotel Tax are local tax components. Restaurant and Hotel are a potential sector for the improvement of local revenue. The objective of research is to understand the contribution, growth rates and effectiveness of restaurant and hotel taxes to local tax and Local Genuine Income. It is expected that research will provide benefit and input for the local government of Surakarta City, especially to the Official of Local Income. The data used in this study is time seriesfrom thedistrict government Surakarta takenbetween 2013 until 2015. While research is descriptive reserch and here is the analysis of secondary data. Data obtained fromthe Depatement of Revenue, Financial Management, and Assets (DPPKAD) Surakarta and other supporting data are taken from various agencies associated with this resetch. The Result of research indicates that restaurant and hotel taxes in Surakarta have quite great potential compared to other tax types. It is consistent to research objective which is to analyze and to explain the contribution, effectiveness and growth rates of restaurant and hotel taxes to Local Genuine Income. The average contribution rate of restaurant tax to Local Genuine Income is 6,45% and contribution rate of hotel tax is 6,17%. Calculation of the growth rate of restaurant tax in 2014 at 19,27% and in 2015 at 12,39%, and for hotel tax growth rateat 2014 at 6,85% and in 2015 at -11,60%.The average effectiveness rate of restaurant tax to Local Genuine Income is 117,37% and contribution rate of hotel tax is 102,09% .